Taxonomic survey on the genus Limonium in the Maltese islands, with description of a new species - Agius, Dolores Rita; Galea, Maria Elizabeth; Cambria, Salvatore; Galdo, Gianpietro Giusso Del; Brullo, Salvatore (Phytotaxa, 2023)
The native species of the genus Limonium (Plumbaginaceae) occurring in the Maltese Islands are investigated. According to current literature, this genus is hitherto represented in this territory by L. virgatum, L. zeraphae and L. melitense, but recent field surveys led to the discovery of a new species growing exclusively on the islet of Cominotto and described as L. lanfrancoi. The latter, for some morphological features regarding the vegetative and reproductive traits, shows closer relationships with L. melitensis, from which, however, it differs in several diacritical characters. For each species, a detailed illustration and a new morphological description based on rich herbarium materials are provided, as well as information on their typification, synonymy, phenology, ecology, distribution, conservation status and a list of examined herbarium specimens is given. Besides, an updating analytical key has been elaborated.